The foreign policy of the 12th Government in the Middle East - Ellias Aghili Dehnavi, Alireza Koohkan, (Opción, 2020)
The present study has been an analytical descriptive one and uses the library method to investigate the foreign policy of the 12th Government in the Middle East, considering the new geopolitics of the region. The results of the study illustrate that the moderation policy of the 12th government has been affected by the emergence of the new geopolitical geopolitics, and especially in countries such as Saudi Arabia and the UAE, it could not be effective. In conclusion, the foreign policy of Iran in the first place requires a realistic understanding of the possibilities and limitations that the country’s geopolitical situation offers.